Insight into the partial replacement of cement by ferronickel slags from New Caledonia. Issue 8 (11th June 2022) - Bouasria, Manal; Babouri, Laidi; Khadraoui, Fouzia; Chateigner, Daniel; Gascoin, Stéphanie; Pralong, Valérie; Benzaama, Mohammed-Hichem; Orberger, Beate; El Mendili, Yassine
Abstract: We investigate the mechanical characterisation of mortars incorporating ferronickel slags (FNS) as partial substitution for cement. The studied slags come from the ferronickel production in New Caledonia. The microstructural characterisation shows that these slags are polycrystalline heterogeneous material mainly composed of forsterite, quartz and enstatite in addition to silica glass. Cement is replaced by up to 20 wt.% of ferronickel slags in the mortars. This upper level of substitution is achieved without compromising mortar's strengths. For all mixes, the maximum compressive and flexural strengths at all curing ages is obtained with a 5 wt.% replacement of cement by ferronickel slags. The larger effectiveness of FNS is attributed to its larger silica content, which increases the polymerisation degree of the silica chains in the calcium silicate hydrate (C-S-H) structure. Slag recycling reduces the storage time, waste management and environmental impact. It significantly lowers costs related to metallurgical processing. Slag substitution for cement, also lowers the carbon footprint.